2014
DOI: 10.1021/ja508369z
|View full text |Cite
|
Sign up to set email alerts
|

Designer HF-Based Fluorination Reagent: Highly Regioselective Synthesis of Fluoroalkenes and gem-Difluoromethylene Compounds from Alkynes

Abstract: Hydrogen fluoride (HF) and selected nonbasic and weakly coordinating (toward cationic metal) hydrogen-bond acceptors (e.g., DMPU) can form stable complexes through hydrogen bonding. The DMPU/HF complex is a new nucleophilic fluorination reagent that has high acidity and is compatible with cationic metal catalysts. The gold-catalyzed mono- and dihydrofluorination of alkynes using the DMPU/HF complex yields synthetically important fluoroalkenes and gem-difluoromethlylene compounds regioselectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
132
2
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 181 publications
(136 citation statements)
references
References 52 publications
0
132
2
2
Order By: Relevance
“…We also demonstrated the synthetic utility and effectiveness of DMPU/HF in some nucleophilic fluorination reactions: the gold-catalyzed hydrofluorination of alkynes [13], fluoro-Prins cyclization reactions [14] and ring-opening fluorination of aziridines [15]. DMPU/HF exhibited high reactivity and selectivity compared with the other aforementioned HF-based reagents.…”
Section: Introductionmentioning
confidence: 99%
“…We also demonstrated the synthetic utility and effectiveness of DMPU/HF in some nucleophilic fluorination reactions: the gold-catalyzed hydrofluorination of alkynes [13], fluoro-Prins cyclization reactions [14] and ring-opening fluorination of aziridines [15]. DMPU/HF exhibited high reactivity and selectivity compared with the other aforementioned HF-based reagents.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen fluoride (HF) is one the most atom-economic fluorination reagent. Furthermore, HF can be regarded as compatible with cationic gold catalysts; this was demonstrated by the synthesis of fluoroalkenes through the gold catalyzed addition of HF to alkynes [11] and the synthesis of α-fluoroketone via HF insertion to a gold carbene intermediate. [12] These methods proved efficient when a terminal alkyne were utilized as substrate; internal alkynes showed low or no reactivity, and the regioselectivity depended on steric and electronic biases at either end of the alkyne.…”
mentioning
confidence: 99%
“…Recently, we developed a new HF-based reagent—DMPU-HF (DMPU = 1,3-dimethyl-3,4,5,6-tetrahydro-2(1H)-pyrimidi-none, now commercially available 26 ), and demonstrated that it was an efficient nucleophilic fluorination reagent in the gold-catalyzed hydrofluorination of alkynes 27 and fluoro-Prins cyclization reactions. 28 We chose the hydrofluorination of 2-methyl N -tosylaziridine 1a as our model reaction (Table 1).…”
mentioning
confidence: 99%